Myth semantics of the astral image in the poetry by Yurii Klen - Цепкало, Тетяна Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article views the features of Yurii Klen creative manner, astral images, their symbolic significance and role in forming of the author’s worldview are analyzed. The mythological basis of archetypal images of the sun, the moon and the stars in the lyrics of the artist, their original interpretation and creation of individual mythological paradigm are explored and explained. Astral symbols are interpreted in accordance with the Slavonic beliefs and ideas, and also with the heritage of the world cultural tradition. An attempt is made to decipher the symbolic code of astral images in the lyrics by Yurii Klen. Attention is given to the reflection of life cycles in the interpretation of heavenly bodies.The realization of astral images in the poetry of Yurii Klen testifies to the artistic and philosophical achievements of the ancient, European and national classics, taking into account the aesthetic innovations of time. The peculiarity of the artist's mythopoetics is a combination of heavenly and earthly, personal and universal, sensitivity, lyricism, metaphorical, allegorical and others. The author’s rethinking of the general cultural mankind achievements is studied, cultural associations and the artist's appeal to the most prominent poets of the world are analyzed. The ontological sides of functioning of mythologems of the sun, the moon and stars in creator’s and their influence on author’s picture of the world are studied in details. The dramatist’s creative work is studied in the view of mythology. Special attention is paid to the creation of author’s own mythology and its influence on the composition’s main conception.